POVERTY ANALYSIS OF FISHERMEN IN INDONESIA - Marjulia Riska Ukhra; Jariah Abubakar (RADJA PUBLIKA, 2025)
This study was conducted to analyze the influence of fishermen's income, HDI, fishery production, and national fish consumption rates on fishermen's poverty in Indonesia. The research location was in Indonesia. This study used secondary data in the form of time series covering 24 years, from 2000 to 2023. Data processing was carried out using Eviews multiple linear regression analysis. The results of the study prove that, partially, the variable of fishermen's income has a negative and insignificant effect on fishermen's poverty, the variable of HDI has a positive and significant effect on fishermen's poverty, the variable of fishery production has a positive and insignificant effect on fishermen's poverty, while the variable of national fish consumption has a positive and insignificant effect on fishermen's poverty. Simultaneously, the variables of fishermen's income, HDI, fisheries production, and national fish consumption have a positive and significant effect on poverty in Indonesia.